Estimation of cadmium, zinc and copper in the blood of workers in the fertilizer industry - Mousa Al-Hamish; Riad Abdul Jabbar; Salih Al-Obaidi (College of Education for Pure Sciences, 2007)
Abstract The present study is consulted to measure the concentration of Cd , Zn and Cu in Workers Blood samples of The General Company for fertilizer industry /Northen region , Baiji . Blood samples were collected from (289) workers of this company then divided to five groups according to the site of work , the workers also divided to two groups according to exposure periods: (5) and (10) years. The results showed a significant increase in the concentration of Cadmium in exposed workers through exposure periods (5) and (10) years in Ammonia factory and utility unite group, Urea factory and Packing unit group and Maintenance and workshops in comparison with control group. According to Zinc concentration , the results showed a significant increase in all groups except Administration departments group, while , the concentration of Copper were decreased through exposure periods in Ammonia factory and utility unite, Urea factory and Packing unit and Maintenance and workshops group comparing with the control groups .